2018
DOI: 10.1186/s41231-018-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

Verification of foetal Down syndrome biomarker proteins in maternal plasma and applications in prenatal screening for Down syndrome

Abstract: Background: Down Syndrome (DS) has a very high morbidity, according to statistics, the incidence rate of DS is as high as 1:700 among the new born babies. At present, there are still no effective prevention or treatment methods for the disease. We used a Western Blot technique to validate differentially expressed proteins between DS foetal umbilical cord blood plasma and healthy foetal peripheral blood plasma from pregnant women to identify new prenatal diagnostic biomarkers for down syndrome (DS) and establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…CLUS, an acute phase protein, is involved in diseases related to oxidative stress [ 81 ]. In this case, the disturbed protein profile observed in the maternal compartment resulting from T21 pregnancy could be related to the many comorbidities observed in T21 fetuses [ 79 , 82 , 83 ].…”
Section: Proteomics and Down Syndrome Screeningmentioning
confidence: 99%
See 4 more Smart Citations
“…CLUS, an acute phase protein, is involved in diseases related to oxidative stress [ 81 ]. In this case, the disturbed protein profile observed in the maternal compartment resulting from T21 pregnancy could be related to the many comorbidities observed in T21 fetuses [ 79 , 82 , 83 ].…”
Section: Proteomics and Down Syndrome Screeningmentioning
confidence: 99%
“…Sui et al reported increased levels of seven proteins (oxoglutarate dehydrogenase L (OGDHL), serum amyloid P component (SAP), ApoE, nucleosome assembly protein 1-like 1 (NAP1L1), thymosin beta 10 (Tβ10), complement factor B, and endoplasmic reticulum oxidoreductase 1 alpha (ERO1L)) in maternal plasma and umbilical cord blood obtained from T21 pregnancies [ 83 ]. The study was conducted on maternal peripheral blood (eight with fetal DS and eight with normal fetuses) using Western blotting.…”
Section: Proteomics and Down Syndrome Screeningmentioning
confidence: 99%
See 3 more Smart Citations